A performance on awareness of e-waste management among university students - Tukimin M.H.B.M.; Anwar R.M.; Latif A.A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Electronic waste management is the practice in managing waste generated from electronic appliances, which may involve the recycle, reuse and reduce of the devices. Although there have been initiatives introduced by countries such as Basel convention or Stockholm convention, the issue of e-waste management is increasing globally. Most of the e-waste was contributed by the high usage of mobile phone or tablet, and the demand keep increasing especially among young generation. This necessitates a study on the awareness among young generation, specifically on university students in gauging their awareness level of the impact of e-waste on human and environmental health. A survey has been carried out among students in a private institution in Malaysia to assess their awareness on e-waste management. As a result, students were aware on the concepts but still are unclear on the e-waste management practices in Malaysia. Based on the survey outcome, the university and the students should play a bigger role in understanding and being directly involved in e-waste management. BEIESP.